2009
DOI: 10.2217/pgs.09.82
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C8 Pharmacogenetics: A Review of Clinical Studies

Abstract: Cytochrome P450 (CYP) 2C8 is responsible for the oxidative metabolism of many clinically available drugs from a diverse number of drug classes (e.g., thiazolidinediones, meglitinides, NSAIDs, antimalarials and chemotherapeutic taxanes). The CYP2C8 enzyme is encoded by the CYP2C8 gene, and several common nonsynonymous polymorphisms (e.g., CYP2C8*2 and CYP2C8*3) exist in this gene. The CYP2C8*2 and *3 alleles have been associated in vitro with decreased metabolism of paclitaxel and arachidonic acid. Recently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 104 publications
2
103
2
Order By: Relevance
“…CYP450 2C8 (CYP2C8), in particular, has emerged relatively recently as an important enzyme that is responsible for the metabolism of a diverse group of drugs in humans, including repaglinide, pioglitazone, rosiglitazone, paclitaxel, dasabuvir, and the androgen-signaling inhibitor enzalutamide (Daily and Aquilante, 2009;Gibbons et al, 2015). Available data suggest that genetic variation in CYP2C8 can alter drug disposition in vivo (Niemi et al, 2003(Niemi et al, , 2005Kirchheiner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CYP450 2C8 (CYP2C8), in particular, has emerged relatively recently as an important enzyme that is responsible for the metabolism of a diverse group of drugs in humans, including repaglinide, pioglitazone, rosiglitazone, paclitaxel, dasabuvir, and the androgen-signaling inhibitor enzalutamide (Daily and Aquilante, 2009;Gibbons et al, 2015). Available data suggest that genetic variation in CYP2C8 can alter drug disposition in vivo (Niemi et al, 2003(Niemi et al, , 2005Kirchheiner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ki.se/cyp2c8.htm). These CYP2C8 genetic polymorphisms have been implicated in the variability of CYP2C8 activity with different phenotypes (Daily and Aquilante, 2009). These different phenotypes are distributed unequally in major ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent report (35), at the locus of the CYP2C8 gene there are 16 allelic variants. These variants are responsible for interindividual and interethnic variability in drug response (36), since their frequencies vary significantly between races and population groups. Clinically the most important variants are CYP2C8*2 to *5 (37,38).…”
Section: Cyp2c8mentioning
confidence: 99%
“…Reports of hepatotoxic effects of diclofenac (36,48,49) have raised the question whether the gene variants CYP2C8*3, CYP2C9*2,*3 or UGT2B7*2, which code for low-activity enzymes, could worsen these effects. Aithal et al (50) found no such association with CYP2C9*2 or *3 variants, but Daily et al (36) did.…”
Section: Diclofenacmentioning
confidence: 99%